Destination Marketing: Optimizing Resource Allocation Using Modern Portfolio Theory. (July 2022) - Johar, Khairil; Tan, David; Maung, Yun; Douglas, Ian
Despite the significant contribution that tourism generates for national economic health, the tourism industry is challenged by seasonal and periodic volatility in arrivals. This volatility causes inefficiencies in the allocation of a destination's resources. Policy makers and operators prefer a steady and constant inflow of tourists. Though prior studies have applied a portfolio optimization approach to inbound tourism flows, this study is the first to consider the destination's marketing budget and each tourism markets' heterogeneous marketing expenditure–demand elasticity. Our model provides destination marketing organizations with direct guidance as to how to allocate their marketing budget to facilitate portfolio profiles that are efficient from a risk-reward perspective, and that are attainable given budget constraints and known marketing expenditure–demand elasticity patterns. Using Tourism Research Australia International Visitor Survey data, we find that variability in tourism fluctuations can be reduced and inbound tourism numbers/spending significantly increased by implementing smarter (data-driven) marketing budget allocations.